Activation of volcanic ash as support for FeOx gliding arc plasma deposition and application in the catalytic oxidation of Rhodamine 6 G - Pitap-Mbowou, Mélanie; Boyom-Tatchemo, Franck W.; Acayanka, Elie; Kamgang-Youbi, Georges; Poupin, Christophe; Gámez-Rivera, Sebastián A.; Cousin, Renaud; Gaigneaux, Eric M.; Laminsi, Samuel (Journal of environmental chemical engineering, 2024)
This study reports the chemical activation of volcanic ash (VA), a local material to promote the subsequent deposition of FeOx nanoparticles through a gliding arc plasma-assisted route to obtain an efficient Fenton catalyst for a better degradation of Rhodamine 6 G in aqueous solution. Plasma-oxidation of Fe(II) solution within the pores of activated VA was performed, then followed the maturation of crystallites (deposited precipitated) thanks to plasma post-discharge species. The obtained materials were characterized by Fourier- Transform Infrared transmission spectroscopy (FTIR), X-ray diffraction (XRD), Nitrogen Physisorption, Thermogravimetric analyses, Scanning electron microscopy (SEM) and Energy Dispersive X-ray spectroscopy (EDX). The acid activation of volcanic ash for 2 h (AM-2) using H2SO4 solution, followed by gliding arc plasma-assisted hydrolytic precipitation of Iron oxide during 30 min (AM-FeOx-30/0) significantly decreased the size of agglomerates particles of VA, leading to the increase by two orders the magnitude the total pore volume as well as the specific surface area. SEM and EDX analyses attested to the incorporation of Fe within the activated volcanic ash framework. The studies also show that plasma-deposited iron oxide nanoparticles are located within different phases of VA. For the obtained AM-FeOx-30/0 material after 30 min of gliding arc plasma deposition on activated VA, Iron oxides are located within the Augite and Goethite phases. While, for the material obtained after plasma-deposition (30 min) followed by ageing at 100°C through a water boiling bath for 4 h (AM-FeOx-30/4), Iron oxides are located within sodium Diopside and Goethite phases. Fenton catalytic activity of the different materials was evaluated for degradation of Rhodamine 6 G and revealed degradation degrees of 31, 95, 79, and 80 % respectively for VA, AM-2, AM-FeOx-0/2 and AM-FeOx-30/4 in the optimum condition (t=20 min, pH=7, [catalyst]=3 g/L, [Rh6G] = 25 mg/L, 1 mL of H2O2 at 30 %. Recyclability tests confirmed the stable catalytic activity of plasma-supported material after 4 runs. These results highlight the valorisation of volcanic ash for the improvement of Fenton catalytic degradation of organic pollutants in solution. [Display omitted] •Acid activation of volcanic ash (VA) by H2SO4 results in micro- and mesoporous aluminosilicate material.•Plasma-assisted precipitation (GPAP) of Fe2+ on porous aluminosilicates leads to the formation of porous amorphous goethite.•Acid activation of VA followed by GPAP of Fe2+ induces an increase of surface area, porosity and catalytic Fenton’s activity.•Temporal post-discharge (TPD) ageing of supported FeOx at 100°C leads to maturation of the FeOx inside the pores.•The material supported by GPAP and TPD aged remains stable after 4 Fenton's catalytic recycling tests.